Observation of excitonic effects in metallic single-walled carbon nanotubes - May, Patrick; Telg, Hagen; Zhong, Guofang; Robertson, John; Thomsen, Christian; Maultzsch, Janina (Physical Review B, 2010)
Excitonic effects of metallic single-walled carbon nanotubes are measured with temperature-dependent resonant Raman spectroscopy. By changing the temperature in the range of 300-870 K, we observe variations in the optical transition energy E(ii) as well as in the maximum Raman intensity. We find both dependences to be different for semiconducting and metallic single-walled carbon nanotubes. We suggest an interpretation in terms of excitons dissociated into free electron-hole pairs at temperatures related to the exciton binding energy. We furthermore discuss how the oscillator strength is influenced by temperature.